EFEKTIVITAS PEMBELAJARAN DARING DI PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA UNIVERSITAS WIDYA DHARMA KLATEN - Wisnu Nugroho Aji Wisnu; Danang Suseno (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2022)
This study aims to determine the effectiveness of online lectures at the Indonesian Language and Literature Education Study Program, Widya Dharma University, Klaten. The questions to be answered through this research are: 1) Has the implementation of online lectures at the Indonesian Language and Literature Education Study Program at Widya Dharma Klaten University proven effective? 2) What are the advantages and disadvantages of online lectures at the Indonesian Language and Literature Education Study Program, Widya Dharma University Klaten? 3) What areas need to be improved so that the implementation of online lectures runs better? This research uses qualitative research methods with interview and documentation data collection techniques. The research subjects are lecturers and students at the Indonesian Language and Literature Education Study Program, Widya Dharma University, Klaten. The data analysis technique in this study used a qualitative descriptive data analysis interactive model from Milles and Michael Huberman which consisted of three concurrent activity lines, namely; data reduction, data presentation, and conclusion drawing. The research findings show that 1) The implementation of online learning in online lectures at the Indonesian Language and Literature Education Study Program, Widya Dharma University, Klaten, is less effective. 2) The advantages of online learning in online lectures at the Indonesian Language and Literature Education Study Program, Widya Dharma University Klaten A, are flexible study times, students are closer to their parents, students do not depend on teachers and train students' self-confidence. While the drawbacks of implementing online learning are teachers cannot interact directly with students, and the internet network is not stable. 3) Areas to improve so that online learning runs better is the use of more interesting learning media such as animated videos, slide shows, power point.